COMPARATIVE ANALYSIS OF THE EFFECT OF BANK FINANCIAL PERFORMANCE ON PROFIT EARNING RATES AT PT. BANK SYARIAH INDONESIA, Tbk AND PT. BANK CIMB NIAGA, Tbk - Syukron Sazly; Seno Sudarmono Hadi; Hasta Herlan; Warsono Warsono; Diana Tambunan; Susanti Susanti (Universitas Muhammadiyah Tangerang, 2023)
Currently, PT Bank Syariah Indonesia Tbk (BSI) has succeeded in becoming the 6th largest bank in Indonesia, passing PT Bank CIMB Niaga Tbk (BNGA), which is a conventional bank. Based on the financial reports up to the fourth quarter of 2022, Bank Syariah Indonesia posted a significant increase in assets from the previous Rp. 265.28 trillion to Rp. 305.72 trillion, which means it has overtaken CIMB Niaga., which recorded assets of Rp. 306.75 trillion until the quarter IV 2022. However, it turns out that Bank CIMB Niaga in the 1st quarter of 2023 has regained this position and is above the BSI, and this position is expected to change one after the other. This is interesting because it is related to BSI's vision of becoming a world-class Islamic bank, which will shift the position of conventional banks which have always been above Islamic banks. The purpose of this research is to compare the financial performance of the two banks to their level of profit (ROA). The sample data is the financial performance of BSI and Bank CIMB Niaga for the first quarter of 2021 to the first quarter of 2023. The data is taken from the first quarter of 2018 - the fourth quarter of 2021. Capital Adequency Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Operating Costs/Income (BOPO) and Loan to Deposit Ratio (LDR) are independent variables and the level of profit earned is represented by Return On Assets (ROA) as the dependent variable. The statistical test is the normality test, multicollinearity, Multiple Linear Regression , determinants, t test (t-test) and F test (F-test) with a significance of 0.05. The result is that simultaneously all financial performance indicators (CAR, NPL, NIM, BOPO, LDR) on BSI and Bank CIMB Niaga have a significant influence significant. However, partially, there is no significant effect of all the financial performance on the level of profit (ROA) of the two banks